Thyroid Disorders and the Distribution of Orally Administered Radioiodine - Bagwe, B. A.; DaCosta, H. (Nuklearmedizin - NuclearMedicine, 1977)
128 control, thyrotoxic, hypothyroid and goitrous euthyroid children were administered 1–2 μCi Na 131I orally and studied in a shadow-shield whole-body counter. 48-hr whole-body counts permitted the differentiation of the first 3 groups (p < 0.005). Ratio of extrathyroid:excreted 131I was 3 times greater in thyrotoxics than in goitrous euthyroids, but the thyroid:extrathyroid ratio was 3 times greater in the latter group. The whole-body profile scan obtained at 48 hr on an attached strip chart recorder, revealed activity not only in the thyroid but even lower down in the vicinity of the knees and feet.